The endophenotype and the phenotype: Temporal discrimination and adult‐onset dystonia. Issue 13 (9th October 2013) - Hutchinson, Michael; Kimmich, Okka; Molloy, Anna; Whelan, Robert; Molloy, Fiona; Lynch, Tim; Healy, Daniel G.; Walsh, Cathal; Edwards, Mark J.; Ozelius, Laurie; Reilly, Richard B.; O'Riordan, Seán
ABSTRACT The pathogenesis and the genetic basis of adult‐onset primary torsion dystonia remain poorly understood. Because of markedly reduced penetrance in this disorder, a number of endophenotypes have been proposed; many of these may be epiphenomena secondary to disease manifestation. Mediational endophenotypes represent gene expression; the study of trait (endophenotypic) rather than state (phenotypic) characteristics avoids the misattribution of secondary adaptive cerebral changes to pathogenesis. We argue that abnormal temporal discrimination is a mediational endophenotype; its use facilitates examination of the effects of age, gender, and environment on disease penetrance in adult‐onset dystonia. Using abnormal temporal discrimination in unaffected first‐degree relatives as a marker for gene mutation carriage may inform exome sequencing techniques in families with few affected individuals. We further hypothesize that abnormal temporal discrimination reflects dysfunction in an evolutionarily conserved subcortical‐basal ganglia circuit for the detection of salient novel environmental change. The mechanisms of dysfunction in this pathway should be a focus for future research in the pathogenesis of adult‐onset primary torsion dystonia. © 2013 International Parkinson and Movement Disorder Society